2003
DOI: 10.1046/j.1523-1755.2003.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse kidney expresses mRNA of four highly related sodium-glucose cotransporters: Regulation by cadmium

Abstract: Reabsorption of glucose in mouse kidney may involve four SGLTs. Cadmium affects mRNA expression of all four SGLTs in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 32 publications
1
31
1
Order By: Relevance
“…lated proteins, and thus indicates the possibility of misinterpretation of immunocytochemical staining. Extrarenal expression of Sglt2 mRNA in several species has been previously proposed in kidney, liver, lung, spleen, eye, and mammary gland of several species (12,25,41,51,54,57); however, the cellular location of SGLT2 protein has not been determined. A more recent study with quantitative PCR analysis indicated a highly kidney-specific expression of Sglt2 mRNA in humans (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lated proteins, and thus indicates the possibility of misinterpretation of immunocytochemical staining. Extrarenal expression of Sglt2 mRNA in several species has been previously proposed in kidney, liver, lung, spleen, eye, and mammary gland of several species (12,25,41,51,54,57); however, the cellular location of SGLT2 protein has not been determined. A more recent study with quantitative PCR analysis indicated a highly kidney-specific expression of Sglt2 mRNA in humans (13).…”
Section: Discussionmentioning
confidence: 99%
“…NaGLT1, a low-affinity Na ϩ -D-glucose cotransporter that does not trans-port D-galactose, has been cloned from rat and is highly expressed in kidney, where it is located in the BBM of proximal tubules (22). SGLT2 has been cloned from human (25,51), pig (26,31), rat (54), mouse (41), and bovine (57). The distribution of SGLT2 was mainly investigated on the mRNA level by Northern blot analysis and in situ hybridization.…”
mentioning
confidence: 99%
“…IM-PTEC cells form confluent monolayers and express the tight junction protein ZO-1 ( Figure 1E). Transcripts for the proximal tubular epithelial markers megalin (gp330) and sodium-glucose exchange transporters (SGLT) 1 and 2 20 were detected ( Figure 1B). These results show that IM-PTEC cultured under restrictive conditions are of proximal tubular origin and display the related characteristics and morphology in culture.…”
Section: Epac-rap Signaling Is Functional In Conditionally Immortalizmentioning
confidence: 99%
“…Glucose is freely filtered by the glomerulus, and reabsorption occurs predominantly on the brushborder membrane of the convoluted segment of the proximal tubule by specific transporter proteins. More distal segments reabsorb almost all of the remainder, resulting in a fractional glucose excretion of Ͻ0.1% (44,45). The sodium-dependent cotransporters (SGLTs), consisting of three subtypes, couple the uphill reabsorption of glucose from the renal tubule lumen with the downhill transport of sodium (19,20).…”
mentioning
confidence: 99%
“…In the later part of the proximal tubule (S3 segment), a high-affinity/lowcapacity cotransporter called SGLT1 is responsible for apical glucose uptake. Because this transporter has a Na ϩ -glucose stoichiometry of 2:1, it can generate a far larger glucose gradient across the apical membrane (45). In addition to SGLT1 and SGLT2, another closely related low-affinity sodiumglucose transporter, SGLT3, originally named SAAT1, has been identified in the proximal tubule, coupling two Na ϩ to one glucose molecule (15,44,45).…”
mentioning
confidence: 99%